Tumor-Primed NK Cells: Waiting for the Green Light - Sabry, May; Lowdell, Mark W. (Frontiers in Immunology, 2013)
The functional impairment of natural killer (NK) cells has been frequently reported in cancer studies. As one of the central components of host anti-tumor immunity, NK cells exert cellular cytotoxicity against tumor cells, and secrete a cytokine milieu to inhibit tumor progression and enable the recruitment of other immune cells to the tumor site. The unlocking of the full functional potential of NK cells requires successful progression through discrete activation stages that are tightly regulated by a complex array of signaling molecules. Target cell susceptibility to NK cell-mediated killing is dependent on the intensity and specific combination of ligand expression for NK cell receptors. Tumor cells utilize numerous strategies for evading NK cells, including the downregulation of important NK cell-activating ligands. Here, we review key studies on NK cell activation requirements, and argue, based on our findings from NK cell-tumor interactions, that the altered characteristics of tumor-associated NK cells are indicative of unmet signaling requirements for full NK cell activation, rather than NK cell dysfunction in cancer.